Development of Popular Scientific Book on ZPT of Shallot Skin Extract on Green Mustard Growth - Istiqamah, Istiqamah; Shalehah, Auliatun (Journal of Biological Science and Education, 2024)
As much as 60% of waste in Indonesia is organic waste, one of which is onion skin waste. Onion skin is often thrown away and not reused. Based on references, shallot skin contains the hormones auxin and gibberellin, which are growth hormones that can be utilised as growth regulators. Popular scientific books on growth regulators from shallot skin extract are still minimal so it is necessary to develop this book. The purpose of this study was to describe the validity and readability of the Popular Science Book digital ZPT of shallot skin extract on the growth of green mustard. The type of research used is Educational Design Research (EDR) development research which includes preliminary research, product prototype design phase (prototyping phase), and product assessment phase by experts (assessment phase) but in this study only up to the product prototype design phase (prototyping phase). This research uses Tessmer's formative evaluation which includes self-evaluation, expert review and one to one evaluation. Validity data was taken from expert validation data as many as three experts using questionnaire instruments. one to one evaluation data to obtain book readability data was obtained from 6 people including 3 students and 3 people from the community. Data on the validity and readability of the book were analysed using Akbar's category. The results showed that the results of the validity test of popular scientific books were 79.85% with a fairly valid category and the readability test data was obtained at 88.88%, showing very good quality.